Used macroinvertebrates as bioindicators to compare water quality from different land uses in Watumokala and Nokambu Rivers, Southeast Sulawesi, Indonesia - KAHIRUN KAHIRUN; BASRUDIN BASRUDIN; LA ODE SIWI; LIES INDRIYANI; SAHINDOMI BANA; LA BACO SUDIA; LA ODE MUHAMMAD ERIF; LA ODE MIDI; NUR MAULINA; NURLIN JAMALUDDIN (Society for Indonesian Biodiversity, 2023)
Abstract. Kahirun, Basrudin, Siwi LO, Indriyani L, Bana S, Sudia LB, Erif LOM, Midi LO, Maulina N, Jamaluddin N. 2023. Used macroinvertebrates as bioindicators to compare water quality from different land uses in Watumokala and Nokambu Rivers, Southeast Sulawesi, Indonesia. Biodiversitas 24: 5693-5708. Macroinvertebrates are animals that live in waters, both on the surface of the water, in riverbeds attached to substrates or mud, and in several biotypes, which are used as bioindicators of water quality due to anthropogenic disturbances that can change land use around rivers. This study aimed to describe the physicochemical parameters and macroinvertebrate community in the Watumokala and Nokambu rivers in Southeast Sulawesi, Indonesia, and to compare the water quality in the two rivers based on ecological index measurements. This study used a survey method at the upstream, middle, and downstream sampling locations for each river with different land use. Data collection on macroinvertebrates and physicochemical parameters was carried out at each station in each river. The data analysis carried out in this study was to calculate the Shannon-Wienner diversity index, species abundance index, uniformity index, Margalef richness index, and the Family Biotic Index (FBI). The results of this study indicated that in the Watumokala River, there were 17 families from 9 macroinvertebrate orders with an abundance of 1852 individuals, more than in the Nokambu River where 14 families were found from 8 orders with an abundance of 904 individuals. There is an influence of land use habitat on macroinvertebrates in the Watumokala and Nokambu Rivers. In the Watumokala River station 1 and station 3 are similar and have a significant correlation with several indicators indicating that the water quality is still good, while at station 2 there is a positive correlation with physicochemical parameters which indicates that the water quality is slightly polluted. Likewise, in the Nokambu River, at station 1 and station 2, there are similarities and significant correlations between physicochemical parameters and macroinvertebrate communities in providing indicators that water quality is still good, while station 3 shows a significant correlation with physicochemical parameters and macroinvertebrates as indicators of water quality polluted. So, the results of this research are useful in efforts to manage land and water in rivers that are experiencing pollution.